2020
DOI: 10.1093/nar/gkaa1129
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional repressors VAL1 and VAL2 recruit PRC2 for genome-wide Polycomb silencing in Arabidopsis

Abstract: The Polycomb repressive complex 2 (PRC2) catalyzes histone H3 Lys27 trimethylation (H3K27me3) to repress gene transcription in multicellular eukaryotes. Despite its importance in gene silencing and cellular differentiation, how PRC2 is recruited to target loci is still not fully understood. Here, we report genome-wide evidence for the recruitment of PRC2 by the transcriptional repressors VIVIPAROUS1/ABI3-LIKE1 (VAL1) and VAL2 in Arabidopsis thaliana. We show that the val1 val2 double mutant possesses somatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 67 publications
8
49
0
1
Order By: Relevance
“…Although there was no difference in the temporal pattern of H3K27me3 deposition at MIR156A in val1-5(sd); val2-3 , the rate of H3K27me3 deposition at MIR156C was significantly slower in this double mutant ( Fig 3B ). These results are consistent with a recent genome-wide study that revealed a decrease in H3K27me3 levels at MIR156C , but not MIR156A , in val1-2; val2-3 plants [ 35 ]. As a control, we measured H3K27me3 deposition at the floral regulator FLC .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Although there was no difference in the temporal pattern of H3K27me3 deposition at MIR156A in val1-5(sd); val2-3 , the rate of H3K27me3 deposition at MIR156C was significantly slower in this double mutant ( Fig 3B ). These results are consistent with a recent genome-wide study that revealed a decrease in H3K27me3 levels at MIR156C , but not MIR156A , in val1-2; val2-3 plants [ 35 ]. As a control, we measured H3K27me3 deposition at the floral regulator FLC .…”
Section: Resultssupporting
confidence: 93%
“…Previous analyses of VAL gene function have utilized val1-2; val2-1 and val1-2; val2-3 double mutants. However, seedling development is so strongly perturbed in val1-2; val2-1 and val1-2; val2-3 plants [ 16 , 25 , 35 , 38 ] that analyses of vegetative growth is problematic in these backgrounds. Therefore, we generated new val1; val2 combinations using val2-3 and a previously uncharacterized T-DNA insertion allele we named val2-4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, telobox motifs are bound by either TELOMERE REPEAT BINDING PROTEIN (TRB) factors or C2H2 zinc-finger family (C1-2iD subfamily) members that guide PRC2 to implement H3K27me3 deposition, which represents an evolutionarily ancient mechanism of telomeric repeats for PRC2-mediated H3K27me3 loading [120,[123][124][125]. Moreover, the RY-repeat motif recruits the PRC2 complex through the intermediation of VIVIPAROUS1/ABI3-LIKE (VAL) transcription factors [126][127][128][129][130][131][132][133]. In agreement, mutants of either trb1/2/3, bpc1-1bpc2bpc4bpc6, or val1val2 in Arabidopsis genetically mimic the phenotypes of those strong PRC2 mutants; however, chromatin loci occupied by these proteins jointly overlap with around 60% of H3K27me3 targets [125,129,134,135].…”
Section: Targeting Mechanisms Of H3k27me3 Deposition On Genomementioning
confidence: 99%